Chaotic Image Encryption with Hash Keying as Key Generator. Issue 2 (4th March 2017) - Gopalakrishnan, T.; Ramakrishnan, S.
ABSTRACT: This paper proposes an image encryption algorithm using Hash key as key generator for permutation and diffusion. SHA-1 algorithm is used to generate symmetric secret key for encryption/decryption process. One-dimensional Logistic map periodic window problem is addressed by employing multiple chaotic maps. In the permutation process, the permutation order is generated in bitwise using Logistic-Sine maps. For diffusion process, the diffusion bits are generated by Logistic-Tent and Tent-Sine maps. Multiple chaotic maps are used for permutation and diffusion to encrypt the images. The image encryption is repeated for four rounds and in each round, different keys are selected to resist chosen plain text attack. The image is encrypted for both gray and color images and satisfactory level of security is achieved. Simulation results are tested for key space analysis, key sensitivity analysis, histogram analysis, quantity analysis, correlation coefficient and average correlation analysis, information entropy analysis and differential attack analysis. The performance analysis tests revealed that the proposed algorithm is robust against cryptanalysis attacks.